2020
DOI: 10.1186/s13048-020-00620-z
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of fertility preservation in women with endometriosis: comparison of progestin-primed ovarian stimulation versus antagonist protocols

Abstract: Background: PPOS protocols, initially described for FP in women with cancer, have many advantages compared to antagonist protocols. PPOS protocols were not evaluated for women with endometriosis. The objective of the study was to describe fertility preservation outcomes in women with endometriosis and to compare an antagonist protocol with a Progestin-Primed Ovarian Stimulation (PPOS) protocol. Method: We conducted a prospective cohort study associated with a cost-effectiveness analysis in a tertiary-care univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 23 publications
2
40
0
Order By: Relevance
“…Wen et al [ 12 ] and Begueria et al [ 8 ] included participants with a maximum age of 35 years. Iwami et al [ 3 ] and Mathieu d’Argent et al [ 11 ] included participants with maximum ages of 41 and 40 years. Peng et al [ 5 ] included participants aged ≥ 40 years.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Wen et al [ 12 ] and Begueria et al [ 8 ] included participants with a maximum age of 35 years. Iwami et al [ 3 ] and Mathieu d’Argent et al [ 11 ] included participants with maximum ages of 41 and 40 years. Peng et al [ 5 ] included participants aged ≥ 40 years.…”
Section: Resultsmentioning
confidence: 99%
“…PPOS can effectively prevent the activation and transmission phases of oestradiol (E2)-induced LH surges and thus serves as an alternative to conventional treatment with GnRH analogs. Prior studies have shown that the PPOS protocol with medroxyprogesterone acetate (MPA) produces competent oocytes/embryos and achieves comparable pregnancy outcomes to those of GnRH antagonist protocols [ 3 , 4 , 7 11 ], as well as short-term protocols [ 12 , 13 ] and mild stimulation protocols [ 5 ] (see Table 1 ). Coupled with the application of frozen-thawed embryo transfer (FET) and the dual trigger of GnRH agonist with low-dose hCG, the PPOS protocol also allows for nearly complete avoidance of OHSS occurrence [ 14 , 15 ], since all the embryo transfers after PPOS are frozen.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been widely used in patients receiving in vitro fertilization (IVF) since 2016 and showed good IVF outcomes [ 3 , 4 ]. Indeed, a PPOS protocol may be considered more “user friendly” for the patients in view of its advantage of fewer injections than a conventional protocol [ 5 ]. In this study, we showed the efficacy of PPOS protocol in various patients and validated its safety in embryonic morphology.…”
Section: Introductionmentioning
confidence: 99%